Contributions To The Study Of The Relevance Of The Web 2.0 On Online Newspapers In Portugal – Case Study - Pinto, Júlio Costa (European Scientific Journal, ESJ, 2016)
With the present investigation we intend to address the effects that Web 2.0 has had in cyber-journalism. Its interest stems from the fact that the Web 2.0 has contributed to the evolution of journalism as well as to the entire communication process by offering experimentation and interaction environments hence promoting the democratization of information. More specifically, we question to what extent have Portuguese online newspapers taken full advantage of the potential and features of the Web 2.0. The investigation will be divided into two structural parts: analysis of the origin and potential of the Web 2.0 and analysis of the Portuguese online newspapers. Insofar as the methodology is concerned, we have opted for a descriptive approach with a review of the literature on the Web 2.0 contribution towards the evolution of the communication process followed up by the analysis of its main features applied to specific newspapers. The sample comprises five Portuguese daily generalist paid newspapers with online version which also offer a paper version with national distribution. We then proceed to an empirical comparative observation of some of the tools made available by Web 2.0. Subsequently, we raise the question to whether – given the present state of affairs – does it make sense to take a step forward into the Web 3.0 concept as a new communicative practice.